Zik a selection from the speeches of Nnamdi Azikiwe - Azikiwe, Nnamdi (Cambridge University Press, 1961)
Zik of Africa as Dr Nnamdi Azikiwe is widely known was Governor-General of the independent federation of Nigeria. From his return to Africa from America in 1934, Zik worked ceaselessly as journalist and politician for the freedom of his native Nigeria and for the advancement of all African peoples. 'Zikism' and African nationalism have often appeared to be synonymous. In what do the leaders of the new Africa believe, and what do they intend? Dr Azikiwe speaks forcefully, often controversially, but never without significance. Students of African affairs throughout the world and his many devoted followers in the African continent will welcome this volume of speeches made by this statesman orator. The speeches and extracts have been arranges in chapters each dealing with on important topic.
Keywords: Nigeria--Politics and government